Enforcement of the Violence Against Persons Prohibition (VAPP) Act 2015 in Fighting Domestic Violence Against Women in Rivers State: Challenges and Remedies (International Journal of Scientific Research and Management (IJSRM), 2018)
Domestic Violence Against women is a global problem that affects all countries of the world including Nigeria. In this work, the challenges of enforcing the Violence Against Persons Prohibition Act (VAPP) 2015 in fighting domestic violence against women in Rivers State were investigated and the remedies were determined. This study adopted the survey research design and a cluster sampling technique. A total of 1200 copies of questionnaire were administered to respondents with a response rate of 92.5% and the data was analyzed using simple percentages, charts and tables. The results show that a total of 69% of respondents disagreed that the VAPP Act of 2015 have been effectively enforced in Rivers State. The study has also shown that although the VAPP Act of 2015 is a welcome development, the level of enforcement in fighting domestic violence against women has been very low since 2015. Based on the findings from this work, the factors responsible for low level of enforcement includes: low level of awareness of the provision of the Act, the jurisdiction of the Act and the fact the women are afraid of been divorce should they take their husbands to court for marital abuses. The study recommended that aggressive awareness campaigns at all levels (villages /communities, towns and cities) should be carried out by government agencies, sociologist, human right Activist and all stakeholders, and the Rivers State government should domesticate the VAPP Act of 2015 to enable women at the local community level seek redress on matters affecting them would lead to improvement in the expected level of enforcement of this Act.